Quality Of Licensing Services At The Cirebon City Investment And One-Stop Integrated Service Office (DPMPTSP) - Karimatusy Syarifah; Siti Khumayah (Jurnal Polisci, 2026)
Public services are a concrete expression of the state’s desire to actively exercise the administrative rights of its residents. This study aims to analyse the quality of licensing services at the Cirebon City Investment and One-Stop Integrated Services Office (DPMPTSP) with the SERVQUAL theoretical framework which consists of 5 basic indicators, namely physical evidence, reliability, responsiveness, assurance and empathy. This research is descriptive qualitative research with the support of the Community Satisfaction Survey 2025 with data collection techniques through in-depth interviews, direct observation, and data triangulation. The result of this study indicates that the Cirebon City DPMPTSP has been responsive and community-oriented in the provision of licensing services. The benefits of this service can be seen from the professionalism of the apparatus, transparency of costs, timeliness of completion, the use of digital technology (OSS, PTSP Mandiri, and Dashboard Monitoring), and the empathetic assistance for the applicant. However, there are still limitations in physical facilities and infrastructure, which have been compensated by significant improvement in service digitalisation. The findings of this study show that Cirebon City DPMPTSP is able to provide efficient, accountable and humane public services despite the budget constraints, by putting community as the main beneficiary of the service and maintaining the dignity of every applicant as a citizen who is entitled to quality services.